Learning Management System (LMS) In The Post-Pandemic Era: An Evaluative Review Of User Experience And Learning Outcomes - Ratna Unaida; Fakhrah Fakhrah; Isna Lukman (LPPM Universitas Malikussaleh, 2024)
One of the online learning platforms that adopts a conventional learning approach but is managed online is the Learning Management System (LMS). LMS is not only easy to use but also encourages independent learning in a social environment for students, providing them with full control over their learning process. This study aims to explore the user experience of LMS post-pandemic. The method used in this study is descriptive qualitative research, which aims to uncover the facts, conditions, variables, and phenomena occurring at present. The subjects of this study are all teachers and students from high schools in the Dewantara District. The results of the study indicate that students are very enthusiastic about the learning process using the LMS application, as they find it easier to understand the material, which positively impacts their learning outcomes. Additionally, teachers show greater creativity in delivering learning materials. The use of LMS also facilitates teachers in assigning tasks to students, making the learning process more varied and no longer monotonous.